PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF TEACHING ENGLISH IN A VIRTUAL REALITY ENVIRONMENT - Alimova , Maftuna (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article provides a theoretical examination of the pedagogical and psychological mechanisms involved in teaching English through virtual reality technologies. The didactic potential of virtual learning environments and their role in enhancing learners’ cognitive engagement, intrinsic motivation, and communicative competence are analyzed. Particular emphasis is placed on the psychological impact of VR-based instruction, including the effectiveness of immersion, emotional involvement, and interactive learning mechanisms. The findings of the study contribute to the development of methodological recommendations for integrating innovative technologies into English language teaching practice. This article presents a comprehensive theoretical analysis of the psychological and pedagogical foundations of teaching English in a virtual reality (VR) environment. The study explores the didactic possibilities of immersive technologies and examines how VR-based instruction transforms traditional language learning into an interactive, experience-oriented process. Particular attention is given to the integration of activity-based learning, interactivity, visualization, and learner-centered approaches within virtual educational spaces. The paper analyzes the cognitive, affective, and motivational dimensions of VR-supported English language teaching. It highlights how immersion, emotional engagement, and simulated real-life communicative situations contribute to the development of learners’ intrinsic motivation, self-efficacy, and communicative competence. The role of social interaction, observation, and collaborative learning in virtual contexts is also examined from the perspective of contemporary psychological theories. Furthermore, the article substantiates that the effectiveness of VR-based English instruction depends on the coordinated implementation of pedagogical objectives and psychological mechanisms. The findings emphasize that immersive virtual environments not only enhance learners’ speech activity and language retention but also reduce psychological barriers and increase confidence in communication. The study provides methodological insights for integrating virtual reality technologies into modern English language teaching practice and outlines перспективные directions for further innovation in digital pedagogy.